Current and promising pharmacotherapeutic options for candidiasis - Scorzoni, Liliana [UNESP]; Fuchs, Beth Burgwyn; Junqueira, Juliana Campos [UNESP]; Mylonakis, Eleftherios (Taylor & Francis, 2021)
Introduction: Candida spp. are commensal yeasts capable of causing infections such as superficial, oral, vaginal, or systemic infections. Despite medical advances, the antifungal pharmacopeia remains limited and the development of alternative strategies is needed. Areas covered: We discuss available treatments for Candida spp. infections, highlighting advantages and limitations related to pharmacokinetics, cytotoxicity, and antimicrobial resistance. Moreover, we present new perspectives to improve the activity of the available antifungals, discussing their immunomodulatory potential and advances on drug delivery carriers. New therapeutic approaches are presented including recent synthesized antifungal compounds (Enchochleated-Amphotericin B, tetrazoles, rezafungin, enfumafungin, manogepix and arylamidine); drug repurposing using a diversity of antibacterial, antiviral and non-antimicrobial drugs; combination therapies with different compounds or photodynamic therapy; and innovations based on nano-particulate delivery systems. Expert opinion: With the lack of novel drugs, the available assets must be leveraged to their best advantage through modifications that enhance delivery, efficacy, and solubility. However, these efforts are met with continuous challenges presented by microbes in their infinite plight to resist and survive therapeutic drugs. The pharmacotherapeutic options in development need to focus on new antimicrobial targets. The success of each antimicrobial agent brings strategic insights to the next phased approach in treatingCandida spp. infections.
Keywords: antifungal compounds; Candida spp; drug combination; drug delivery; drug repurposing